The Journey Within: Inner Calling as Spiritual in R. K. Narayan’s The Guide and Robin Sharma’s The Monk Who Sold His Ferrari - Sharma, Kamal (Literary Studies, 2021)
The Journey within begins when people start contemplating about the real purpose of their existence. The contemplation of longing to know the real purpose of life starts in the process of sitting with mindfulness – meditation which transcends the survival purpose of life. It leads to spirituality, the ability to talk to oneself or the heart - the inner calling, leads humans towards the perception of Divine within oneself, treasure within oneself and happiness within oneself. R. K. Narayan’s The Guide and Robin Sharma’s The Monk Who Sold His Ferrari carve out spiritual traces where protagonists find pleasure and happiness. In The Guide, the transformation of Raju from a tourist guide to spiritual guide for the sake of humankind and his interconnectedness with the Divine owes much to the self-realization as well as to his heart. In the same way, The Monk Who Sold His Ferrari transcends the material prosperity and reaches to the state of ecstasy as exemplified in spiritual preaching of the monk - Robin. Following the spirituality as theoretical tool, the article the central characters and explores their transformation towards spiritual awakening.